1994
DOI: 10.1126/science.8303298
|View full text |Cite
|
Sign up to set email alerts
|

Promoter-Selective Transcriptional Defect in Cell Cycle Mutant ts13 Rescued by hTAF II 250

Abstract: The TAFII250 subunit of the human transcription factor IID (TFIID) rescues the temperature-sensitive hamster cell line ts13 and overcomes a G1 arrest. Investigation of the transcriptional properties of ts13 nuclear extracts in vitro showed that activation by the site-specific regulators Sp1 and Gal4VP16 is temperature sensitive in ts13 extracts, whereas basal transcription remains unaffected. This transcriptional defect can be rescued by purified human TFIID or by expression of wild-type TAFII250 in ts13 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
154
2
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 27 publications
(22 reference statements)
14
154
2
2
Order By: Relevance
“…8b), indicating that the decrease in cyclin A RNA expression is due to reduced transcription, a conclusion consistent with the reported defect in cyclin A promoter activity in ts13 cell extracts at the restrictive temperature (Wang & Tjian 1994). However, cyclin A protein was synthesized normally starting at 10 h when the cells were incubated for 5 h at 33.5 8 C followed by a shift up to 39.5 8 C (Fig.…”
Section: Following Serum Stimulationsupporting
confidence: 87%
See 1 more Smart Citation
“…8b), indicating that the decrease in cyclin A RNA expression is due to reduced transcription, a conclusion consistent with the reported defect in cyclin A promoter activity in ts13 cell extracts at the restrictive temperature (Wang & Tjian 1994). However, cyclin A protein was synthesized normally starting at 10 h when the cells were incubated for 5 h at 33.5 8 C followed by a shift up to 39.5 8 C (Fig.…”
Section: Following Serum Stimulationsupporting
confidence: 87%
“…Sp1, AP-1 and CREB were present at normal levels at 39.5 8 C in tsBN462 cells, but Oct-1 DNA-binding activity was decreased (T.S., unpublished observation), suggesting that the expression of Oct-1 requires CCG1/TAFII250. The fact that Sp1 levels were normal at 39.5 8 C, yet Sp1-mediated transcription is reportedly decreased in vitro in ts13 cell extracts (Wang & Tjian 1994) might suggest that an interaction between Sp1 and CCG1/ TAFII250 is affected by the mutation. This defect, combined with the loss of Oct-1, could contribute to the decreased cyclin D1 transcription at 39.5 8 C. Rb may also play a role, since Rb activates the cyclin D1 promoter .…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that among the activators tested, transcriptional repression by overexpression of TAF II 40/60 is specific for activation by p53-GAL4, consistent with the roles of TAF II 40 and TAF II 60 in transcriptional activation by p53 in vitro (58). Furthermore, these results demonstrate that inhibition of transcription by TAF II 230 is a general phenomenon, consistent with the role that TAF II 230 has been suggested to play in activated transcription in vitro (7,61). However, our results differ with the proposed roles of TAF II 40 in activation by VP16 (20) and of TAF II 110 in activation by Sp1 (18,28).…”
Section: -Tbp-taf Interaction In Vivo 4299supporting
confidence: 74%
“…The functional relevance of this interaction was made evident from data showing that missense mutations in Sp1 that disrupt the interaction between TAF II 110 and Sp1 impair the ability of Sp1 to activate transcription (18). Whereas direct interactions between transactivators and Drosophila TAF II 230, or its human homolog TAF II 250, have not been observed, this TAF is essential for activated transcription in vitro (6,56,58,61). It has been speculated that TAF II 230/ TAF II 250 functions as a scaffold protein, binding directly to TBP and recruiting other TAFs to the TFIID complex (6,27,34,36,49,63).…”
mentioning
confidence: 97%
“…While the cell cycle regulatory functions of TAF II s are not fully understood, progress has been made. Molecular and genetic analysis revealed that yTAF145, hTAF250 and mTAF30 are required for the transcription of G 1 /S cyclin genes, and inactivation of conditional alleles in these genes in their respective organisms resulted in cell cycle arrest in G 1 (Martin et al, 1999;Walker et al, 1997;Wang and Tijan, 1994;Sekiguchi et al, 1996;SuzukiYagawa et al, 1997). These important observations have provided an attractive model of how these TAF II s control cell cycle progression, by controlling the transcription of cyclins and other cell cycle regulatory genes.…”
Section: Introductionmentioning
confidence: 99%